Three-dimensional ultrasound in the prenatal diagnosis of osteogenesis imperfecta - Pei-Yin Tsai; Chiung-Hsin Chang; Chen-Hsiang Yu; Yueh-Chin Cheng; Fong-Ming Chang (Elsevier, 2012)
Objective: Fetal osteogenesis imperfecta (OI) is a heterogeneous group of collagen disorders characterized by bone fragility, blue sclerae, deafness, and dentinogenesis imperfecta. Ultrasonography is acknowledged as a reliable diagnostic modality for the prenatal diagnosis of OI, especially type II. In the past, two-dimensional (2D) ultrasound (US) has been applied as the mainstay of prenatal diagnosis of OI. In this series, we report our work of detecting OI using three-dimensional (3D) US. Material and Methods: We reviewed our computer database of prenatal diagnosis of OI at the National Cheng Kung University Hospital from April 1996 to July 2010. All the cases were scanned by 2D and 3D US. In total, six cases of fetal OI were diagnosed. Results: Compared with 2D US, 3D US can detect fetal OI precisely, and provide additional vivid illustration after various modes of reconstruction that 2D US cannot. Conclusion: In conclusion, 3D US may contribute significantly to the detection of OI in utero and provide a novel visual depiction of this defect after reconstruction. The technique may thus substantially assist in prenatal diagnosis as well as consultations for fetal OI.